Avilés Canyon System: Increasing the benthic biodiversity knowledge. (5th September 2022) - Ríos, Pilar; Altuna, Álvaro; Frutos, Inmaculada; Manjón-Cabeza, Eugenia; García-Guillén, Laura; Macías-Ramírez, Aurora; Ibarrola, Teodoro P.; Gofas, Serge; Taboada, Sergi; Souto, Javier; Álvarez, Fernando; Saiz-Salinas, Jose I.; et al.
Abstract: Macro and megafauna were studied in the Avilés Canyon System (ACS), southern Bay of Biscay (Cantabrian Sea), during several oceanographic cruises carried out from 2009 to 2017. The biodiversity of ACS is summarized and its description is herein updated after sampling surveys of several programmes (ECOMARG, INDEMARES, SponGES, INTEMARES) conducted by the Spanish Institute of Oceanography (IEO). This study has updated previous knowledge in the canyon area from past national and international projects, their reports and publications as well as data collected in the context of regional projects designed to gain new insight into the diversity of marine invertebrates and fishes from the ACS. Samples were taken using a range of sampling gears (Rock dredge, Beam trawl, Trawl gear GOC-73, Suprabenthic sledge, Box corer and Remoted operated vehicle), from 55 to 2291 m in depth. A total of 1015 species were identified at the ACS: 98 Porifera, 153 Cnidaria, 14 Brachiopoda, 22 Bryozoa, 97 Mollusca, 151 Annelida, 315 Arthropoda, 74 Echinodermata and 91 Chordata. New records for the Bay of Biscay fauna include 13 Porifera species, 17 Cnidaria, 7 Mollusca, 8 Arthopoda, 3 Echinodermata and 4 Chordata. Also the bathymetric range of some species has been extended. As a result of the research projects carried out in the area in the last fifteen years, important information is now available which suggests that the ACS houses a large number of species with a high ecological value, that it represents a biodiversity hotspot in terms of the presence of sponge aggregations and coral reefs in certain regions, and that it sustains important fisheries due to the abundance of comercial species. Given the relevance of the species and habitats occurring in the ACS, there is a need to implement a conservation and management plan of the area in order to maintain habitats in good state of preservation. Highlights: A list of 1015 identified species in the ACS is completed with indication of depth range. 52 are new record for ACS.